KINESIOTAPING FOR BREAST CANCER RELATED LYMPHEDEMA - Erkan Kaya; Cengiz Kaplan; Özgür Dandin (European Journal of Breast Health, 2012)

(untitled)
Lymphedema is a disability resulting in some patients that undergo the surgical procedure mastectomy, with a difficult treatment. In recent years, kinesiotaping has been used particularly in sport injuries, and its pain management is an alternative treatment modality. However, its effect mechanisms are not exactly known. Additional to the pain management, kinesiotaping effectively decreases disability in the treatment of lymphedema by creating alternative drainage pathways. We report three cases, which have used kinesiotaping for the treatment of left upper extremity lymphedema after mastectomy.